2023
DOI: 10.1177/21501351231157587
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Obstructed Right Ventricle to Pulmonary Artery Conduits: The Modified Peel Operation

Abstract: Reconstruction of the right outflow tract with extracardiac conduits has made complete repair of complex cardiac malformations possible. However, reoperation is usually required for a right ventricle-to-pulmonary artery conduit obstruction. We describe a modified peel operation, where the sides and posterior half of the previously placed conduit are preserved, and a prosthetic roof is placed over the conduit remnant. This has been our current technique to manage conduit obstructions. It is a safe operation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In patients with extremely calcified xenograft conduits (but also in those with circumferentially calcified homografts), the peel technique is a valuable option that consists of preserving the sides and posterior half of the previously placed conduit while a prosthetic roof is placed over the conduit remnant. Cervantes-Salazar et al found this technique safe and easy to teach residents (25).…”
Section: Xenograft Pericardial Conduitsmentioning
confidence: 97%
“…In patients with extremely calcified xenograft conduits (but also in those with circumferentially calcified homografts), the peel technique is a valuable option that consists of preserving the sides and posterior half of the previously placed conduit while a prosthetic roof is placed over the conduit remnant. Cervantes-Salazar et al found this technique safe and easy to teach residents (25).…”
Section: Xenograft Pericardial Conduitsmentioning
confidence: 97%